A utilização distorcida da lei da alienação parental enquanto instrumento de violação dos direitos de crianças, adolescentes e mulheres - Bastos, Eliene Ferreira (2022)
This research proposes to analyze Law nº 12.318/2010 through interdisciplinary bibliographic research and the review of criticisms against its use, with the approach of gender bias and domestic, family and intra-family violence. The opposing and favorable positions to the parental alienation law point to the need for its improvement towards effective gender equity in the exercise of co-parenting. This need aims to meet the constitutional principles of equality between men and women and, above all, the best interests and the integral protection of children and adolescents. This thesis concludes that the best alternative is the adoption of a device of declaration of parental capacity in invoking the law of parental alienation